Energy consumption and pass-trough effect of fuel price in Malaysia - Poh, Paik Xuan (2015)
The issue on energy has been hotly debated whether on its production, consumption or price due to its importance in our daily life. Essentially the purpose of this thesis is twofold. First and foremost, the first objective investigates the long run relationship between energy consumption and the economic output in Malaysia by including trade openness. This is motivated by the concern of the narrowing gap between energy consumption and production as well as the importance of the export led growth strategy. The annual data employed from 1980 until 2011 utilizing the Fully Modified Ordinary Least Square (FMOLS) as the main method and Dynamic Ordinary Least Square (DOLS) for robustness check. The finding drawn shows that energy is a restrictive factor to economic development and the export led growth strategy implemented contribute to the vital role of trade openness as a stimulus to economic growth. Hence government can provide incentive at various levels to encourage the usage of renewable energy as well the research and development (R&D) to increase the usage of renewable energy. Besides that, a more active role can be played by the government through ASEAN Free Trade (AFTA) in order to harvest good relationship with the neighboring countries to ensure conducive trade liberalization environment. On the other hand, the second objective studies the pass-through effect of actual diesel price and retail diesel price into Malaysia’s consumer price. As the government is rationalizing the subsidy on fuel, this inspires this study to compare the effect of actual diesel price and retail diesel price on consumer price. The well-established Autoregressive Distributed Lags (ARDL) method is adopted by incorporating the quarterly data spanning from 2005 until 2013. The results indicated that the transmission effect of actual diesel price is bigger where no subsidy is given comparatively to the retail diesel price whereby the price is subsidizes by the government. The sub-price indexes that are most affected by the transmission of the actual diesel price is the food and non-alcoholic price index as well as the transport price index. Therefore the policies outline should include efficient distribution and marketing chains of food products besides developing the public transportation,encourage carpooling as well improve the freight transport management. This will essentially reduce reliance of consumers on the fuel.